Konstruksi Identitas Di Era Media Baru: Youtube - Hayati, Laila; Herdiyanti, Herdiyanti; Saputra, Putra Pratama (Jurnal Neo Societal, 2021)
The advanced technology has driven society to the new civilization: human civilization of new media. Currently, the new media can facilitate human beings in maintaining the relationship among them. Social media is one of examples of a well-known new media. The study aims to analyze the role of new media in constructing the users’ identity. The Qualitative phenomenological research was employed to conduct the study. Observation and interview were applied to collect the data. The function of Youtube has transformed from the platform of exchanging information through video to the platform of constructing the users’ identity. It occurs when viewers of Youtube participate actively in following the particular content that forms viewers’ identity based on content they watch. Finally, the identity construction formed by the viewers of Youtube leads to the fake identity and create the inappropriate values or social norms of society.